Multimodal retrieval of autobiographical memories: sensory information contributes differently to the recollection of events - Willander, Johan; Sikström, Sverker; Karlsson, Kristina (Frontiers in Psychology, 2015)
Previous studies on autobiographical memory have focused on unimodal retrieval cues (i.e., cues pertaining to one modality). However, from an ecological perspective multimodal cues (i.e., cues pertaining to several modalities) are highly important to investigate. In the present study we investigated age distributions and experiential ratings of autobiographical memories retrieved with unimodal and multimodal cues. Sixty-two participants were randomized to one of four cue-conditions: visual, olfactory, auditory, and multimodal. The results showed that the peak of the distributions depend on the modality of the retrieval cue. The results indicated that multimodal retrieval seemed to be driven by visual and auditory information to a larger extent and to a lesser extent by olfactory information. Finally, no differences were observed in the number of retrieved memories or experiential ratings across the four cue-conditions.